2019
DOI: 10.1016/j.physa.2019.03.125
|View full text |Cite
|
Sign up to set email alerts
|

Quantum metrology out of equilibrium

Abstract: We address open quantum systems out-of-equilibrium as effective quantum probes for the characterisation of their environment. We discuss estimation schemes for parameters driving a de-phasing evolution of the probe and then focus on qubits, establishing a relationship between the quantum Fisher information and the residual coherence of the probe. Finally, we apply our results to the characterisation of the ohmicity parameter of a bosonic environment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…However, if time is not considered a resource, we found that the best estimate is obtained upon using two qubits in a product states, each one subject to a local environment, i.e. the best strategy is to repeat twice a single-qubit probe measurement [17,18]. Notice that the notions of same bath or two independent replicas of the same bath do not require multiple physical systems to be implemented in practice.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, if time is not considered a resource, we found that the best estimate is obtained upon using two qubits in a product states, each one subject to a local environment, i.e. the best strategy is to repeat twice a single-qubit probe measurement [17,18]. Notice that the notions of same bath or two independent replicas of the same bath do not require multiple physical systems to be implemented in practice.…”
Section: Discussionmentioning
confidence: 94%
“…The single-qubit case has already been described in previous works, dealing with the purely dephasing bath, related both to the estimation of temperature or other bath parameters [16][17][18][19]. Here we focus, under the same conditions, on the two-qubit probe scenario, which allows us to explore the role of quantum correlations and the number of qubits in inferring the temperature.…”
Section: Physical Modelmentioning
confidence: 99%
“…In this context, a relevant feature of our probing technique is the pure dephasing nature of the interaction between the qubit and its environment. This means that, while the ohmic system has a fixed temperature, the probe has access to the full set of out-of-equilibrium states [ 22 ], while not exchanging energy with the ohmic system. As we will see, this provides room to optimize the probing strategy and to enhance sensitivity over classical (thermal) probes.…”
Section: Introductionmentioning
confidence: 99%
“…The topic has become of interest in the last two decades, due to the development of controlled quantum systems at the classical-quantum boundary [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], which makes it relevant to have a precise determination of temperature for quantum systems [21][22][23][24][25][26][27] and to understand the ultimate bounds to precision in the estimation of temperature [28][29][30][31][32][33][34][35][36][37][38][39]. At the same time, precise manipulation of quantum systems makes it possible to design and realize quantum thermometers, i.e., thermometers where temperature is precisely estimated looking at tiny changes in genuine quantum features such as entanglement or coherence [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%